36 Identification and management of patients with elevated BMI in ST. James's hospital. (30th September 2020) - Balfe, C; Corcoran, R; Gilmartin, A; Nadarajan, R
Abstract : The rapid rise in rates of obesity in recent decades represents a major challenge in healthcare provision. In Ireland in 2011, 26% of men and 21% of women were obese. Analysis from the United Kingdom has suggested that by 2050, over half of the adult population may be obese. BMI is widely used to classify individuals as normal weight, underweight, overweight and obese. Severe obesity is defined as a BMI >40 kg/m 2 (or ≥35 kg/m 2 in the presence of comorbidities). We analysed a group of patients admitted to the acute medical assessment unit in St. James's Hospital on unselected general medical take in July and August 2019. We measured the height, weight and body mass index of each patient and reviewed the medical notes to identify if abnormal BMIs were being identified and discussed with patients. We identified the proportion of patients with an elevated BMI who were informed of their condition, and who had a management plan discussed by their primary medical team. We additionally determined if patients with an elevated BMI were being referred to a dietician service. 74 patients (39 men and 35 women) were included in the final analysis. Given the setting of unselected intake, there was significant heterogeneity in the weights of the cohort assessed, with inclusion of patients with low and very elevated BMIs. The BMI spread from the cohort is displayed in figure 1 . We considered a patient's weight to have been addressed by the primary medical team if an overweight or obese status was discussed with the patient and/or documented in the admission note. 10 out of 39 patients who were overweight or obese had this documented in their admission note (26%). No patient had their BMI measured independent of a nutritionist's input. Referral to dietetics was made in 75% of underweight patients, 33% of overweight patients, 11% of patients with class I obesity, 66% of those with class II obesity and 66% of those with class III obesity. 4% of patients had weight loss proposed in their management plan. Hypertension was a comorbidity in 50% of patients, with 34% of patients having a diagnosis of dyslipidaemia. Musculoskeletal disease was present in 26%, most commonly in the form of gout. Documentation of a patient's weight is standard practice during a modern day hospital admission, mainly due to the necessity for weight-based medication dosing and accurate assessment of renal function. However, as it stands it is not the routine to calculate the body mass index during these same admissions. Nonetheless, calculation of the BMI represents the prerequisite to identifying and advocating for patients who are overweight and obese. We argue that it would be optimal for all admitted patients to have their height and weight measured during their admission, with subsequent calculation of the BMI. With an electronic patient record (due to be initiated in all public hospitals in Ireland in the coming years), the BMI could be published on every patients home page. We feel that this would act as an impetus to discussion and management of an often under acknowledged comorbidity.